Perbandingan penggunaan topikal asi dengan perawatan kering terhadap lama pelepasan tali pusat bayi - Febriana Sari; Detty Siti Nurdiati; Dhesy Ari Astuti (Universitas Aisyiyah Yogyakarta, 2016)
This reseach aims to investigate the difference between umbilical cord treatment by using topical ASI and dry treatment towards the length of umbilical cord release in baby. This research used quasi experimental method with non-equivalent posttest design only. 44 samples of neonatal babies were taken by using consecutive sampling according to the inclusion criteria. The average length of umbilical cord release with topical ASI is 6.18 days and the one with dry treatment is 7.41 days. The length of umbilical cord release with topical ASI is 1.23 days faster compared to the one with dry treatment with p=0.010. The umbilical cord release with topical ASI is faster than the one with dry treatment and it can also reduce infection.